Mothers who kill - Beyer, Charlotte 1965-; Savarese, Josephine 1962- (Demeter, 2021)
"This compelling and unique collection of critical and creative work assesses for the first time cultural, literary, legal and historical representations and narratives about mothers who kill and filicide. The idea of a mother killing her child to many presents the greatest taboo, and the most disturbing and distressing aspect of maternal experience. In Toni Morrison’s 1987 novel Beloved, escaped slave mother Sethe addresses her daughter Beloved whom she murdered out of desperation, in order to avoid her returning to a life of slavery and sexual abuse. Sethe reflects, "I’ll explain to her, even though I don’t have to. Why I did it. How if I hadn’t killed her she would have died and that is something I could not bear to happen to her.